Effect of body fat on temporal dispersion of ventricular repolarization duration assessed by QT variability index in healthy females - Hiba Salih Mahdi Al-Khassaki,; Bassam Talib Al-Galani, (Journal of the Pakistan Medical Association, 2024)
Objective: To assess the impact of age as well general and central adiposity indices on QT variability index. Method: The cross-sectional study was conducted at the Department of Physiology, College of Medicine, Mustansiriyah University, Baghdad, Iraq, from September 2020 to April 2021, and comprised healthy adult females having regular menstrual cycle. QT variability index and its association with age, body mass index, waist circumference and waist-height ratio were worked out. Data was analysed using SPSS 14. Results: There were 55 women with mean age 37.4±10.5 years. QT variability index correlated significantly and positively with age, body mass index, waist circumference and waist-height ratio (p<0.05). Conclusion: Aging and obesity increased QT variability index, and could contribute to ventricular arrhythmia and sudden cardiac death. Key Words: Circumference, Adiposity, Cardiac, Menstrual, Arrhythmias, Aging